2022
DOI: 10.1002/nau.25021
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of neurogenic bladder patient‐reported readiness and experience following care in a transitional urology clinic

Abstract: To generate a scoping review that summarizes thematically on all reported patient perceptions on readiness and experiences during transitional urologic care for patients with neurogenic bladder and or congenital genitourinary conditions that require continuity of care into adulthood.Methods: A systematic literature search was performed in October 2021. Records were screened and identified for studies relevant to reported readiness and experience in urologic transitional care among patients needing life-long ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(160 reference statements)
1
5
0
Order By: Relevance
“…This study suggests that despite the abundance of data pertaining to the importance of long-term specialist surveillance and the broad consensus on the need for multidisciplinary clinics from early teenage years across a number of conditions, there remains little agreement regarding how this should be carried out. A recent scoping review from Toronto demonstrated that most adolescent patients felt that sexuality and fertility were not adequately tackled during the transition phase, with reported barriers to successful transition including patient, provider, and system factors, including a lack of insurance coverage/financial management, patient preference, trust and communication with the adult provider [23]. This is broadly in line with the findings of this study in that these questions should be addressed during this time.…”
Section: Discussionsupporting
confidence: 83%
“…This study suggests that despite the abundance of data pertaining to the importance of long-term specialist surveillance and the broad consensus on the need for multidisciplinary clinics from early teenage years across a number of conditions, there remains little agreement regarding how this should be carried out. A recent scoping review from Toronto demonstrated that most adolescent patients felt that sexuality and fertility were not adequately tackled during the transition phase, with reported barriers to successful transition including patient, provider, and system factors, including a lack of insurance coverage/financial management, patient preference, trust and communication with the adult provider [23]. This is broadly in line with the findings of this study in that these questions should be addressed during this time.…”
Section: Discussionsupporting
confidence: 83%
“…The inclusion of temporality into OAB also enables the formulation of transitions in care within this framework. This concept is observed to be emerging notably in the context of neurogenic LUTS 45 . An analogy can be drawn between the transitions in OAB phenotype, from childhood to adulthood and from elderly to frail elderly.…”
Section: Discussionmentioning
confidence: 95%
“…This concept is observed to be emerging notably in the context of neurogenic LUTS. 45 An analogy can be drawn between the transitions in OAB phenotype, from childhood to adulthood and from elderly to frail elderly. In both scenarios, there is a shift between a patient-centered and healthcare-centered system, along with shifts in the perception of disease ownership, understanding of the medical condition, and awareness of available therapeutic approaches.…”
Section: Delphi Domainsmentioning
confidence: 99%
“…They can experience recurrent urinary tract infections (34–70%), urinary incontinence (46–52%), CKD (20%), and other urologic concerns [ 66 , 73 ]. Urologic care transition was shown to decrease the use of emergency services [ 74 ]; however, it is currently associated with a lower satisfaction rate when compared to pediatric urology care [ 75 ], confirming the need for further improvements.…”
Section: Transition Of Carementioning
confidence: 99%